Concurrent multiple intracranial and intramedullary conus tuberculoma: A rare case report - Jaiswal, Manish (Asian J Neurosurg, 2017)
Central nervous system (CNS) tuberculosis commonly manifests as tubercular meningitis. CNS tuberculomas are more common intracranially and less frequently involve the spinal cord. Combination of intramedullary with intracranial tuberculomas is extremely rare. We report a case of concurrent occurrence of intramedullary tuberculoma with multiple intracranial tuberculomas in a young 16-year-old boy, who presented with two weeks history of paresthesias and weakness of the lower limbs and diminution of vision in left eye, who had been treated for pulmonary tuberculosis. Magnetic resonance imaging (MRI) spine showed a well-circumscribed lesion opposite L1, which was diagnosed as intramedullary tuberculoma. As for vision complaint, on cranial imaging, he was found to have multiple round contrast enhancing lesions, which were diagnosed as intracranial tuberculomas based on their typical MRI findings. He had complete recovery with conventional treatment of anti-tubercular therapy and steroids, without any surgical intervention. We suggest that MRI of the brain should be performed in all case of intramedullary spinal tuberculoma because of the possible presence of early asymptomatic/mild symptomatic intra-cranial tuberculomas.